Audit quality attributes of European Union supreme audit institutions - Clark, Colin; Martinis, Michael De; Krambia-Kapardis, Maria; Clark, Colin; Martinis, Michael De (My University, 2007)
To examine the enabling legislation of European Union (EU) member country supreme audit institutions (SAIs) for their accountability to parliament and independence from the executive arm of government.
Keywords: Auditing; Auditing standards; Auditors; European legislation; European Union; Auditing; Auditing standards; Auditors; European legislation; European Union